Profil Glukosa Darah Dan Urea Plasma Pada Sapi Bali Yang Menderita Anestrus Post Partum (THE BLOOD GLUCOSE PROFILE AND PLASMA UREA IN POSPARTUM ANESTRUS OF BALI CATTLE) - Busiasa, Made Kota; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2015)
The aim of this study was to determine the levels of blood glucose and plasma urea in postpartum anestrus bali cattle. The research design used to determine both blood glucose andblood plasma urea concentration is completely randomized design consisting of two groups: groupI, cows have a normal cycle and group II, postpartum anestrus cows experiencing with each groupconsisting of 4 repetitions . The results in the study showed that glucose levels did not appear toshow significant differences between glucose levels during estrus and cattle anestrus postpartum. While the plasma urea levels appear to show significant differences between urea levels duringestrus and cattle anestrus postpartum. Time significantly  for glucose on day- 0 and the day to-14.The same thing seems  urea levels that increase significantly  on day- 0 and to 14. The results canbe concluded that urea levels influence the emergence of postpartum estrus in bali cattle, whereasglucose levels had no effect.
Keywords: glucose; urea; bali cattle